Structural Breaks in Fiscal Performance : Did Fiscal Responsibility Laws Have Anything to Do with Them? - Medina, Leandro (IMF Working Papers; Working Paper ;, 2010)
In recent years, many countries have adopted Fiscal Responsibility Laws to strengthen fiscal institutions and promote fiscal discipline in a credible, predictable and transparent manner. Still, results on the effectiveness of these laws remain tentative. In this paper, we test empirically whether fiscal performance, measured as the level of primary fiscal balances and their volatility, indeed improved after the implementation of Fiscal Responsibility Laws in a sample of Latin American and advanced economies. We show that traditional econometric approaches, which rely on the use of dummies in time series or panel regressions, yield biased estimates. In contrast, our empirical strategy recognizes that, a priori, the timing of the effect of these laws on fiscal performance is unknown, while controlling for the impact of the business and commodity cycles on fiscal outcomes. Overall, we find limited empirical evidence in support of the view that Fiscal Responsibility Laws have had a distinguishable effect on fiscal performance. However, Fiscal Responsibility Laws could still have other positive effects on the conduct of fiscal policy not analyzed here, for instance, through enhanced transparency and guidance in the budget process and lower risk premia.